Biomass-based carbon dot-modified cerium oxide nanoparticles (BCDs@CeO2) efficiently promote Myriophyllum aquaticum to remove NH4+-N and TP in eutrophic water - Xingling Nie; Jun Ma; Ming Chen; B. Larry Li (Ecotoxicology and Environmental Safety)
Aquatic plants are widely used for eutrophication remediation. However, strong abiotic plant stress often limits their remediation efficiency. This study proposed biomass-based carbon dot-modified cerium oxide nanoparticles (BCDs@CeO2) with good biocompatibility to mitigate abiotic plant stress. The BCDs@CeO2 pretreated Myriophyllum aquaticum exhibited enhanced removal rates of NH4+-N and TP, with the 10 mg/L BCDs@CeO2 treatment showing increases of 39.23 % and 29.11 %, respectively, compared to the pure water-precultured plant system (p < 0.05). Plant physiological changes and transcriptomic analysis revealed that BCDs@CeO2 treatment upregulated glycolysis/gluconeogenesis and α-linolenic acid metabolism pathways in rhizomes, inducing increased ATP synthase and antioxidant enzyme (Peroxidase, Catalase, and Superoxide Dismutase) activities, and enhancing amino acid metabolism, which further boosted Glutamine Synthetase activity and promoted NH4+-N and TP absorption and utilization. ICP-MS and microscopic analysis confirmed the uptake and migration of BCDs@CeO2 in plants. In summary, this study provides an effective strategy to enhance eutrophication phytoremediation.